Genetic evidence for conserved non-coding element function across species–the ears have it - Turner, Eric E.; Cox, Timothy (Frontiers in Physiology, 2014)
Comparison of genomic sequences from diverse vertebrate species has revealed numerous highly conserved regions that do not appear to encode proteins or functional RNAs. Often these “conserved non-coding elements”, or CNEs, direct gene expression to specific tissues in transgenic models, demonstrating they have regulatory function. CNEs are frequently found near ‘developmental’ genes, particularly transcription factors, implying that these elements have essential regulatory roles in development. However, actual examples demonstrating CNE regulatory functions across species have been few, and recent loss-of-function studies of several CNEs in mice have shown relatively minor effects. In this Perspectives article, we discuss new findings in ”fancy” rats and Highland cattle demonstrating that function of a CNE near the Hmx1 gene is crucial for normal external ear development and resembles loss-of function Hmx1 coding mutations in mice and humans. These findings provide important support for similar developmental roles of CNEs in divergent species, and reinforce the concept that CNEs should be examined systematically in the ongoing search for genetic causes of human developmental disorders in the era of genome-scale sequencing.